A simple and efficient dual optical signaling chemodosimeter for toxic Hg(II) - Mashraqui, Sabir H.; Tripathi, Sapna A.; Ghorpade, Sushil S.; Britto, Smita R. (Beilstein Journal of Organic Chemistry, 2012)
10-Methylthioacridone, designated as acrithion, has been employed as an easily accessible chemodosimeter for the optical targeting of toxic Hg2+ in buffered aqueous DMSO. The Hg2+-mediated desulfurization of the probe is translated into selective dual signaling of Hg2+ by means of color bleaching and fluorescence amplification while several other metal ions, including potentially competing Ag+, Cu2+ and Pb2+, afford no significant interferences even in excess concentrations.
Keywords: chemidosimeter; chemosensor; fluorescence; Hg(II) selective; UV–visible; visual detection